Chemical Compositions of the n-hexane Fraction of Canna edulis Ker Gawl Rhizomes - Thi Van Anh, Nguyen; Thi Minh Hang, Nguyen; Hong Luyen, Le; Thi Thom, Vu (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 37 No 4, 2021)
In this study, six compounds isolated from the n -hexane fraction of Canna edulis Ker Gawl rhizomes for the first time include 24-methylenecycloartane-3 β -ol, sitoindoside I, citrulloside, 16 β -hydro-19-al- ent- kauran-17-oic acid, daucosterol, and β- sitosterol. Spectroscopic methods as MS and NMR were used to elucidate their structures. Keywords: Canna edulis Ker Gawl, β -sitosterol, daucosterol, sitoindoside I, citrulloside, 24-methylenecycloartane-3 β -ol, 16 β -hydro-19-al- ent- kauran-17-oic acid. References [1] T. H. Vu, Q. U. Le, Edible Canna (Canna edulis Ker), a Potential Crop for Vietnam Food Industry, Int. J. Bot, Vol. 4, No. 4, 2019, pp. 58-59. [2] A. S. A. Snafi, Bioactive Components and Pharmacological Effects of Canna indica - an Overview, Int. J. Pharmacol. Toxicol., Vol. 5, No. 2, 2015, pp. 71-75. [3] N. Tanakar, The Utilization of Edible Canna Plants in Southeastern Asia and Southern China, Econ. Bot, Vol. 58, No. 1, 2004, pp. 112-114. [4] J. Zhang, W. Z. Wu, Q. Mi, Q, Phenolic Compounds from Canna edulis Ker Residue and Their Antioxidant Activity, LWT - Food Sci. Technol., Vol. 44, No. 10, 2011, pp. 2091-2096. [5] J. Zhang, W. Z. Wu, Soluble Dietary Fiber from Canna edulis Ker By-product and Its Physicochemical Properties, Carbohydr. Polym., No. 92, No. 1, 2013, pp. 289-296. [6] F. Xie, S. Gong, W. Zhan, J. Wu, Z. Wang, Potential of Lignin from Canna edulis Ker Residue in the Inhibition of α-d-glucosidase: Kinetics and Interaction Mechanism Merging with Docking Simulation, Int. J. Biol. Macromol., Vol. 95,No. 2017, pp. 592-602. [7] T. M. H. Nguyen, H. L. Le, T. T. Ha, B. H. Bui,N. T. Le, V. H. Nguyen, T. V. A. Nguyen, Inhibitory Effect on Human Platelet Aggregation and Coagulation and Antioxidant Activity of Canna edulis Ker Gawl Rhizhomes and Its Secondary Metabolites, J. Ethnopharmacol., Vol. 263, 2020, pp.113-136. [8] J. D. P. Teresa, J. G. Urones, J. S. Marcos,P. Basabe, M. J. S. Cuarado, R. F. Moro, Triterpenes from Euphorbia broteri, Phytochem, Vol. 26, 1987, pp. 1767-1776. [9] A. T. Nguyen, H. Malonne, P. Duez, R. V. Fastre, M. Vanhaelen, J. Fontaine, Cytotoxic Constituents from Plumbago zeylanica, Fitoterapia, Vol. 75,No. 5, 2004, pp. 500-504. [10] F. J. Momeni, S. F. Kimbu, B. L. Sondengam,M. T. H. Khan, M. I. Choundhary, A. U. Rahman, Potent Inhibitors of Tyrosinase Activity from Citrullus colocynthis Schrad. (Cucurbitaceae), Acta Pharmaceutica Sciencia, Vol, 52, 2010, pp. 328-334. [11] Y. C. Wu, Y. C. Hung, F. R. Chang, M. Cosentino, H. K. Wang, K. H. Lee, Identification of ent-16β,17-dihydroxykauran-19-oic Acid as an Anti-HIV Principle and Isolation of the New Diterpenoids Annosquamosins A and B from Annona squamosa. J. Nat. Prod., Vol. 59, No. 6, 1996, pp. 635-637. [12] F. R. Chang, P. Y. Yang, J. Y. Lin, K. H. Lee,Y. C. Wu, Bioactive Kaurane Diterpenoids from Annona glabra, J Nat Prod, Vol. 61, No. 4, 1998, pp. 437-439. [13] F. M., Moghaddam, M. Farimani, M. Amin, Chemical Constituents of Dichloromethane Extract of Cultivated Satureja khuzistanica. Evid Based Complement Alternat Med., Vol. 4, No. 1, 2007, pp. 95-98. [14] Z. Sheng, Z. Dai, S. Pan, H. Wang, Y. Hu, W. Ma, Isolation and Characterization of an α-glucosidase Inhibitor from Musa spp. (Baxijiao) Flowers, Molecules, Vol. 19, No. 7, 2014, pp. 10563-10573. [15] E. Gupta, β-sitosterol: Predominant Phytosterol of Therapeutic Potential, Innova Food Tech, Vol. 32, 2020, pp. 465-477. [16] J. Zeng, X. Liu, X. Li, Y. Zheng, B. Liu, Y. Xiao, Daucosterol Inhibits the Proliferation, Migration and Invasion of Hepatocellular Carcinoma Cells via Wnt/ β-catenin Signaling,Molecules, Vol. 22, No. 2017, pp. 862. [17] K. H. Kuo, Y. T. Yeh, S. Y. Pan, S. C. Hsieh, Identification and Structural Elucidation of Anti-Inflammatory Compounds from Chinese Olive (Canarium Album L.) Fruit Extracts. Foods, Vol. 8, No. 10, 2019, pp. 441.